The matchmakers of Minnow Bay : a novel - Harms, Kelly (Thomas Dunne Books/St. Martin's Press, 2016)
"A young painter, Lily has reached a crossroads in her life. Her career hasn't taken off, her best friend may no longer be the trusted friend she thought, her boyfriend is a disappointment, and now she can't keep up with the rising cost of living in the city. With no one to turn to, Lily is forced to move from her beloved apartment, but while packing she comes across a piece of mail that had slipped to the back of her junk drawer: a letter detailing further action needed to finalize the annulment of a quickie Vegas wedding. Ten years ago! Lily decides it's time to turn over a new leaf and the first item on her list of things to fix is getting the annulment ... but you can't just send a reply ten years later, "Hey by the way we are still married." This is something that must be addressed in person. Lily takes to the road to track down her husband - the charming, fun, and sexy man she connected with all those years ago - Ben Hutchinson. Ben Hutchinson left a wealthy dot-com lifestyle behind to return home to his family and the small town he loves, Minnow Bay. He's been living off the grid and the last thing he expects is a wife he didn't know he had to show up on his doorstep. By chance, Lily arrives at the magical Minnow Bay Inn, and there she will discover not just a place to lay her head, but new friends, a thriving art community, and maybe even the love of her life"--